A scintillating tale of the early stages of self-directed learning for future doctors in a growing medical college - Jayakumar, Karthi; Kumar G., Amar; Sasirekha; Berlin Raj, Jenneth; Bhaskaran, K. (International Journal of Research in Medical Sciences, 2025)
Background: Self-directed learning (SDL) is a pivotal element in modern medical education, encouraging learners to take ownership of their learning process. In response to the National Medical Commission (NMC)'s mandate, this study aimed to assess the influence of SDL among preclinical and paraclinical students at AMCH (Arunai Medical College and Hospital) Tiruvannamalai, Tamilnadu, India. Methods: Through mixed research methods, we evaluated the awareness of SDL, faculty perceptions, and student learning outcomes. The study involved the implementation of an innovative assessment tool, AMAI (Arunai Metacognitive Assessment Instrument), to track progress in the SDL process and eliminate bias. Results: The study revealed increased student engagement, reflective practices, and improvements in analytical thinking at the metacognitive level. The AMAI assessment tool played a crucial role in ensuring consistency and tracking student development. Conclusions: This research highlights the effectiveness of SDL in medical education, demonstrating its impact on student performance and faculty involvement. The AMAI tool serves as a structured framework for evaluating SDL implementation.